La evaluación formativa y el proceso enseñanza aprendizaje de Matemáticas - Gaona Gaona, Pedro Manuel (2025)
This research focuses on formative assessment and the Mathematics teaching-learning process, whose objectives are: to describe the theoretical foundations of formative assessment that guide the Mathematics teaching-learning process, characterize formative assessment for the Mathematics teaching-learning process, and establish how formative evaluation strengthens the Mathematics teaching-learning process. It was methodologically based from a qualitative approach, design and documentary review method. To synthesize the information, use was made of the recording, the elaboration of search logs and content sheets. Through the documentary review it was possible to obtain the results and discuss them, in this way it was possible to conclude that the formative evaluation focuses on the teaching-learning process and on providing timely and constructive feedback to the students. Its distinctive features include its focus on student progress and development, its formative nature, and its emphasis on feedback as a tool to improve the Mathematics teaching-learning process, as well as its continuous development that takes place throughout the years. the entire educational process